Screening for microbial markers in Miocene sediment exposed during open-cast brown coal mining - Elhottová, Dana; Kristůfek, Václav; Frouz, Jan; Nováková, Alena; Chronáková, Alica (Antonie van Leeuwenhoek, 2006)
Viable microorganisms were found in Miocene lacustrine clays of the cypris formation excavated from 200-m below the surface as spoil during open-cast brown coal mining (Sokolov Brown Coal Basin, North-Western Bohemia, Czech Republic). Both saprotrophic microfungi of the genera Penicillium, Verticillium, Cladosporium and Aspergillus as well as heterotrophic bacteria were isolated from an intact sediment cores. Heterotrophic bacteria were classified by the MIS Sherlock System as representatives of genera Nocardiopsis, Arthrobacter, Micrococcus, Kocuria, Rothia, Clavibacter, Bacillus, Paenibacillus, Brevibacillus, Microbacterium, Acinetobacter and Pseudomonas. A bacterium found among the strains had an atypical fatty acids profile enriched by branched fatty acids and polyunsaturated fatty acid (18:3 omega 6) and gave no MIS Sherlock match. Phospholipid fatty acids analysis indicates a relatively high (535 pmol g(-1)) but inhomogeneously distributed viable microbial biomass. Fatty acids analyses of non-fractioned lipids (representing viable, storage and dead biomass; 8390 pmol g(-1)) detected rich and homogenous profiles with fungal, bacterial and actinomycetal markers but no protozoan and algal fatty acids markers.
Keywords: Fatty Acids; kultivační média; Fossils; Bacteria; počet mikrobiálních kolonií; Culture Media; Bacteriological Techniques; těžba uhlí; Biomarkers; zkameněliny; Colony Count, Microbial; geologické sedimenty; mastné kyseliny; Coal Mining; biologické markery; dějiny starověku; houby; Geologic Sediments; History, Ancient; Fungi; bakteriologické techniky